Growth Opportunities, Capital Structure And Dividend Policy (An applied study on companies listed on the Damascus Securities Exchange) - مرهج منذر; قلاب فارس (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aims to determine the impact of growth opportunities and capital structure on the dividend policy (cash and non-cash dividend) in companies listed on the Damascus Securities Exchange during the period (2010-2019). To achieve this objective, the two researchers used a hypothetical-deductive approach to formulate the hypotheses; and analyzed the financial statements of all companies listed in Damascus Securities Exchanges. The research reached the following results: 1- There is an inverse effect of growth opportunities and capital structure on the dividend payout ratio. 2- Growth opportunities inverse affect the decision to distribute cash dividends. 3- There is no effect of growth opportunities and capital structure on the stock dividend ratio. 4- There is an inverse effect of growth opportunities on the decision to pay cash dividend. 5- There is no effect of capital structure on the decision to pay cash dividend. 6- There is no effect of growth opportunities and capital structure on the decision to distribute stock dividend. 7- There is no effect of growth opportunities and capital structure on the zero dividend decision.